Hubungan antara faktor-faktor terpilih dengan stres dalam kalangan guru sekolah rendah di daerah Jeli, Kelantan - Muhammad Shukri, Deraman (2011)
The purpose of this research was to identify. the relationship between selected factors and stress amongst primary school teachers in Jeli Kelantan. Two instrument were used in this study. The Validating Measures Of Teacher Stress (VMTS) developed by Pettegrew and Wolf (1982) was used to measure the five dimensions of the stress factors namely, role ambiguity, role overload, role conflict, management style and task stress. The Stress Composite Measures of Five Sympton (SCMS) developed by Conley and Woosley (2000) was used to measure the level of teacher's stress. A total of 168 teachers from Jeli District in Kelantan were involved in this research. The data was analysed using descriptive and inferential statistic (frequencies, mean, standard devision, percentage, T-test, ANOVA and Pearson Correlation Coefficient). The results of this study were as follows: 1) The first hypothesis was failed to reject because there was no significant difference of teacher's stress based on gender. 2) The second hypothesis was failed to reject because there was no significant difference of teacher's stress based on teaching experiences. 3) The third hypothesis was fail to rejected because there was no significant differences of teacher's stress based on teacher' education level. 4) The fourth hypothesis was failed to reject because there was no significant correlation between the teacher's stress and role ambiguity. 5) The fifth hypothesis was rejected because there was a significant correlation between teachers' stress and role overload. 6) The six hypothesis was rejected because there was a significant correlation between role conflict and teacher stress. 7) The seven hyphothesis failed to reject because there was no significant correlation between management style and teacher's stress. 8) The eight hyphotesis was rejected because there was a significant correlation between task stress and teacher's stress